2010
DOI: 10.1101/gad.1951110
|View full text |Cite
|
Sign up to set email alerts
|

The TCT motif, a key component of an RNA polymerase II transcription system for the translational machinery

Abstract: The TCT motif (polypyrimidine initiator) encompasses the transcription start site of nearly all ribosomal protein genes in Drosophila and mammals. The TCT motif is required for transcription of ribosomal protein gene promoters. The TCT element resembles the Inr (initiator), but is not recognized by TFIID and cannot function in lieu of an Inr. However, a single T-to-A substitution converts the TCT element into a functionally active Inr. Thus, the TCT motif is a novel transcriptional element that is distinct fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
155
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(163 citation statements)
references
References 33 publications
7
155
1
Order By: Relevance
“…71 The core promoters of most ribosomal protein genes in Drosophila and humans contain a functional TCT motif, which is not recognized by the TBP/TFIID complex. 21 Remarkably, TRF2, but not TBP, has recently been shown to mediate the transcription of ribosomal protein genes that lack a TATA box and have functional TCT motifs. 73 In vitro transcription analysis using Drosophila TRF2-depleted embryonic nuclear extracts demonstrated that transcription of 4 TCT-dependent ribosomal genes (RpL30, RpLP1, RpS12 and RpS15) was reduced, while no effect on transcription of TATA-dependent genes was observed.…”
Section: Tbp-related Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…71 The core promoters of most ribosomal protein genes in Drosophila and humans contain a functional TCT motif, which is not recognized by the TBP/TFIID complex. 21 Remarkably, TRF2, but not TBP, has recently been shown to mediate the transcription of ribosomal protein genes that lack a TATA box and have functional TCT motifs. 73 In vitro transcription analysis using Drosophila TRF2-depleted embryonic nuclear extracts demonstrated that transcription of 4 TCT-dependent ribosomal genes (RpL30, RpLP1, RpS12 and RpS15) was reduced, while no effect on transcription of TATA-dependent genes was observed.…”
Section: Tbp-related Factorsmentioning
confidence: 99%
“…The TCT motif is a polypyrimidine initiator located from ¡2 to C6 relative to the TSS, which has been identified in genes encoding ribosomal proteins as well as other proteins involved in translation. 21 Both the MTE and DPE motifs are located at a specific position relative to the Inr (with strict spacing requirements from the A C1 of the Inr) and their function depends on the Inr. The MTE is located from C18 to C27 relative to the A C1 of the Inr, and its consensus sequence is CSARCSSAAC.…”
Section: Introductionmentioning
confidence: 99%
“…Two dinucleotides, CC and TC, are part of a broader TC/ CT motif (Fig. 3C), similar to the TCT initiator, specific to highly expressed protein translation-associated genes (Parry et al 2010). Indeed, the genes that carry these motifs are also protein translation-associated genes in zebrafish (Supplemental Fig.…”
Section: Evolutionary Conservation Of Sequence Characteristics Suggesmentioning
confidence: 99%
“…This initiator motif is common to this functional category of genes in both Drosophila and mammalian genomes. It is characterised by a "sharp" transcription initiation pattern and, in Drosophila, it does not seem to contain a TATA box or any other known fixed-spacing motifs [6]. It has recently been reported that the PIC at this type of promoters lacks TBP, whose place is taken by the structurally related TRF2 [82].…”
Section: Promoter Classes and Modes Of Regulationmentioning
confidence: 99%